A COMPARATIVE STUDY OF GASIFICATION OF FOOD WASTE (FW), POULTRY WASTE (PW), MUNICIPAL SOLID WASTE (MSW) AND USED TIRES (UT) - Naveed, S.; Ramzan, N.; Malik, A.; Akram, M. (The Nucleus, 2020)
The rate and volume of generation of waste material in the developing societies has increased significantly. Correspondingly the demand of energy has increased many folds. One of the options in this situation is to recover the energy value of the waste material for production of power and heat through gasification. Gasification of materials is a proven concept and its environmental benefits are known. The characteristic behavior and scope of gasification of four waste materials namely steam treated Food Waste (FW), Poultry Waste (PW), steam treated Municipal Solid Waste (MSW) and Used Tyres (UT) have been studied in a 10kg/hr hybrid gasification plant. This pilot plant consists of a fixed bed gasifier followed by a two in one cyclone scrubber for gas cleaning and a flare system. Various laboratory tests of these materials through proximate, ultimate analysis and stove test were conducted to establish their fuel characteristics. These materials were gasified to generate synthesis gas. It was observed that FW and UT offer sustainable potential for energy recovery. MSW on the other hand had considerable ash and had difficulties during gasification. PW could only be gasified when mixed with charcoal or high CV UT in order to balance against its high moisture. The gas analysis of the waste indicated significant quantities of hydrogen and carbon monoxide.